Comparative Perspectives: Exploring Workflow Efficiencies of BIM and CAD in 3D Modelling - Henricus Arya Wisnu Wardana; Audrey Maura; Meliana Putri Suman; Steffania Jacinda (Journal of Artificial Intelligence in Architecture, 2024)
Building Information Modelling (BIM) is a new technology to make genuine project contributions, especially in the industry, architecture, and construction sectors. However, in practice, many professional workforces choose computer-aided design (CAD) as the primary technology, which has formerly appeared and is further comprehensible. Building Information Modelling offered different perspectives on purpose to facilitate designers or architects to expertise in various fields. Building Information Modelling (BIM) contains informative data that can use some expertise as a solution to make the occupation more coherent. This research aims to comprehend the workflow differences between Computer Aided Design (CAD) and Building Information Modelling (BIM) system technology. We collated methods by reviewing some literature and reviewing case studies. Then, we compare the workflow and conclude which is more effective for architectural design. In this research, we explore the difference between BIM's workflow and Cad's workflow to know which is more effective. So, we conclude and can apply the technology appropriately in the workflow needed so that it can simplify the workflow.